Prevalence of self-reported diabetes, hypertension and heart disease in individuals seeking State funding in Trinidad and Tobago, West Indies - Derek Chadee; Terence Seemungal; Lexley M. Pinto Pereira; Mary Chadee; Rohan Maharaj; Surujpal Teelucksingh (Springer, 2019)
Objective: Diabetes, hypertension and heart disease inflict a heavy health burden on the Caribbean Republic of Trinidad and Tobago. This study assessed the prevalence of self- reported diabetes, hypertension and heart disease in lower socioeconomically placed individuals accessing welfare grants. Method: Data collected between July 2008 and June 2009 were analyzed from 14,793 responses. The survey sought information on education, average monthly income, health, housing, and household facilities. Results: Self-reported disease prevalence was 19.5% (95% CI: 18.9-20.2) for diabetes mellitus; 30.2% (95% CI: 29.5-30.9) for hypertension; and 8.2% (95% CI: 7.7-8.6) for cardiac disease. Diabetes and cardiac disease had equivalent gender frequency; hypertension was more prevalent in women (p < .001). Disease prevalence was highest in Indo-Trinidadians, married and divorced subjects, non-Christians and increased with age. Those with primary education alone were at greatest risk. Conclusion: Trinidad and Tobago have a high prevalence of hypertension, diabetes and heart disease. Hypertension showed gender specificity in women. Prevalence was highest in Indo-Trinidadians, increased with age, and primary education alone was a risk factor. Interventions to arrest the high prevalence of chronic non-communicable diseases to promote wellness are needed in Trinidad and Tobago.